Postprandial TG and Risk in Patients with CVD - Jacobson, Anne (MD Conference Express, 2011)
The Homburg Cream and Sugar Study [HCS; NCT00628524] provided additional information regarding the relationship of fasting and postprandial triglyceride (TG) levels and risk in patients with cardiovascular disease. The study was designed to determine whether the measurement of postprandial TG levels improved risk prediction of cardiovascular events over traditional risk markers in stable patients with cardiovascular disease.